Síntese eletroquímica e caracterização de filmes finos de compostos da forma BiSe(X), com X = Cu, Fe ou Co - Mendes, Paulo de Carvalho Dias (2015)
The present work is based on the literature related to the Bi2Se3 compound, which is present in current researches as a topological insulator and is also well known for thermoelectricity applications. In this work the electrochemical synthesis of a material containing Bi, Se and X (X = Cu, Fe or Co) was carried out searching for a composition of Bi and Se in accordance with the stoichiometry of Bi2Se3. The third element, X, was used in the electrodeposition baths considering the Bi2Se3 literature, which presents doping and interaction with other elements for this compound. The synthesis conditions were determined based on studies using cyclic voltammetry. The main material studied was the ternary compound containing Bi, Se and Cu. The films obtained were characterized using scanning electron microscopy, energy dispersive x-ray spectroscopy, x-ray diffraction and Raman spectroscopy. It was found out that baths containing sulfuric acid were adequate for obtaining films of Bi, Se and Cu but a bath containing glycerol and sodium citrate was necessary for including Fe on the material. Some magnetic properties of the films obtained were also studied and paramagnetic behaviour was observed for the samples.